Penyuluhan Tentang Tanda Bahaya Kehamilan Di TPMB Hj. Mardiawati - Pratiwi Bayuningrum; Armiyati Nur; Erniawati Erniawati; Siti Nur Azizah (Pusat Riset dan Inovasi Nasional, 2023)
The health of pregnant women is one of the national health indicators. The Center for Indonesian Medical Students' Activities (CIMSA) considers that the health figures for pregnant women in Indonesia cannot be categorized as good. So early detection of pregnancy complications can be used as an effort to prevent complications in pregnancy. The still high maternal mortality rate (MMR) and infant mortality rate (IMR) can be caused by several factors, one of which is the lack of optimal antenatal care and low maternal knowledge about danger signs in pregnancy. Pregnant women's knowledge about danger signs in pregnancy is one of the factors that can influence pregnant women at high risk of experiencing danger signs in pregnancy. The main causes of maternal death, namely preeclampsia, bleeding and infection, can be prevented if the signs are recognized early. These signs are known as danger signs of pregnancy. Therefore, pregnant mothers should learn more about the danger signs of pregnancy. The aim of this activity is to increase mothers' knowledge about the danger signs of pregnancy. This activity was carried out at TBMB Hj. Mardiawati on September 5 2020. The target of this activity is pregnant women who are pregnant women who are at TBMB Hj. Mardiawati. The methods used in this community service activity include counseling, discussion, Javanese questions. After counseling, pregnant women understand and know about the danger signs in pregnancy.